A Electronic Corruption (E-Corruption) in Digital Public Services: Criminal Law Challenges in the Era of Technological Transformation - Syafa`i, Imam; Muhammad Aini (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
The development of digital technology in public services presents great opportunities to increase transparency and accountability but also raises new challenges in the form of increasingly complex electronic corruption (e-corruption). The urgency of this study lies in the need for a deep understanding of the criminal law challenges that arise due to the digitalization of public administration, especially in the context of developing countries. This study aims to analyze the impact of digitalization on the level of corruption in the public service sector and assess the effectiveness of existing legal mechanisms in overcoming e-corruption. The method used is mixed methods with a sequential explanatory approach, involving qualitative analysis through in-depth interviews and literature studies, as well as quantitative surveys of civil servants and users of digital public services. The study results show that digitalization has succeeded in increasing transparency and reducing traditional corruption, but has also given rise to new forms of e-corruption such as data manipulation and misuse of digital identities. The main challenges identified include regulatory gaps, system vulnerabilities, and low digital literacy among the public. These findings emphasize the need for regulatory updates, strengthening digital security systems, and increasing digital literacy to support eradicating corruption in the digital era. This research makes an important contribution to the development of public policies that are adaptive to technological transformation and recommends further research with a broader scope to test the effectiveness of e-corruption prevention strategies.